Analysis of Maharah Qira'ah Learning in Grade VI Students: Challenges and Solutions - Dilla, Ubaidillah Fajar Anky; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the implementation of Maharah Qira'ah (Arabic reading proficiency) learning in Grade VI students of Ula Madrasah Diniyah Salafiyah Islamiyah Tanggulangin Sidoarjo. The research aims to understand the difficulties encountered by students in learning Maharah Qira'ah, both linguistic and non-linguistic, and provide effective solutions to address these challenges. Qualitative research methods, including interviews, observations, and documentation, were employed to gather data from the headmaster, curriculum vice-principal, Arabic teachers, and students. The collected data were analyzed using data reduction, data presentation, and drawing conclusions. The findings revealed that Maharah Qira'ah learning encompassed planning, implementation, and evaluation stages. Linguistic difficulties involved difficulties in recognizing letter shapes, pronunciation, and punctuation, while non-linguistic difficulties encompassed teacher-related, student-related, methodological, and teaching media factors. The proposed solutions included introducing letter shapes, encouraging active student participation, fostering a positive perception of Maharah Qira'ah learning, teaching vocabulary through memorization, explaining sentence structure, providing comprehensive reading materials, offering repetitive and simplified exercises, analyzing words in context, enhancing teacher competence, motivating students, cultivating interest in Maharah Qira'ah, catering to students with limited religious knowledge, and utilizing preferred teaching methods and media. This study highlights the importance of addressing linguistic and non-linguistic difficulties to enhance Maharah Qira'ah learning outcomes. Further research can explore the effectiveness of alternative teaching methods and media preferences to optimize Arabic language acquisition. Highlight: Implementation of Maharah Qira'ah Arabic Learning in Grade VI Linguistic and non-linguistic difficulties in Maharah Qira'ah learning Solutions to overcome difficulties in learning Maharah Qira'ah Keyword: Maharah Qira'ah, Arabic Learning, Linguistic Difficulties, Non-Linguistic Difficulties, Solutions